Pengembangan Media Buku Bantal Hitung (Bubantung) Sebagai Pengenalan Konsep Angka Pada Anak Usia 4-5 - Lia dwihasnawati (STAI Terpadu Yogyakarta, 2023)
The purpose of this study was to better understand (1) practicality and (2) the effectiveness of using counting pillow books to help young children understand the meaning of numbers. The research approach of this research is the ADDIE development model. The stages in the research process include (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The viability and efficacy of picture story book media products were evaluated using expert tests, individual tests, small group tests, field tests, and large group tests. This study used a nonequivalent quasi-experimental control group design. Examination of the validator test both media and content produces research findings. Based on the evaluation of the two media and material validator tests, this was found. obtained by 80.5% in the average media validation test. It is included in the development area that can be achieved from the perspective of Bubantung teaching materials. In addition, the average score obtained from the results of the material validation test was 84%, placing the expert exam from the teaching material test in the feasible category to construct. The validation average of the media test and material test was 82.25%, indicating that this category is feasible for further development